Analisa Kemampuan Berpikir Kritis Siswa dan Kebutuhan Game Edukasi STEM: Kajian Prespektif Guru SMK IPAS di Sumatera Selatan - Melinda maharani; Leni Marlina; Ida Sriyanti (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
Critical thinking is increasingly recognized as an essential skill for vocational high school students. However, teachers in South Sumatra report that students’ performance remains limited, particularly in advanced clarification, decision-making, and complex reasoning. This study represents one of the first regional analyses of IPAS teachers’ perceptions regarding critical thinking and the integration of STEM-based digital games in Indonesian vocational schools. Employing a quantitative descriptive approach, the study involved 118 IPAS teachers from various regions. Findings indicate that 57% of teachers stated that only some students were able to conduct observations and compile reports, while 53% reported that only a few students could anticipate logical consequences. Overall, teachers noted that digital learning facilities such as communication devices, internet access, and presentation media were available, although their distribution varied across schools. Most teachers also expressed positive attitudes toward the use of STEM-based digital educational games, viewing them as an effective medium for enhancing student engagement and strengthening critical thinking in IPAS learning. These results emphasize how important it is to develop STEM-based digital educational games as a strategic solution for improving critical thinking skills in vocational education